Transformation of the meaning of nonsense words through arbitrary comparative relations with happy faces - dos Santos, Gabriela Alves Rodrigues; Perez, William Ferreira; de Almeida, João Henrique; de Rose, Julio César (Perspectivas em Análise do Comportamento, 2017)
The present study aimed to investigate the transformation of meaning via comparison relations among meaningless and faces expressing happiness. Adults were exposed to a task in which two abstract figures were established as contextual cues controlling the selection of different quantities of multiple objects. Then, such stimuli were used to establish the following relational network of comparison involving nonsense words and faces expressing joy: A <B <HAPPY FACE <D <E. After establishing arbitrary relations of comparison and testing derived relations (e.g., A <E, E> A), the participants evaluated the meaning of stimuli A and E using (a) a semantic differential instrument, (b) a preference test and (c) an implicit test (IRAP). The results of the semantic differential suggest the transformation of the function of the stimuli A and E accordingly the comparison relation. In this instrument, stimulus E, a word related arbitrarily as being “more” than happy faces, was evaluated by participants as more positive when compared to stimulus A (established as “less” than happy faces). Preference test, although varying among participants, show a tendency to avoid stimulus A and a preference for stimulus E. Unlike the previous measures, it was not possible to verify a clear difference between the evaluations of stimuli A and E by means of the IRAP, both being evaluated as equally positive in terms of this implicit measure. The observed results demonstrate that although A is less happy than E, it was not considered sad, producing this inconsistency in IRAP results.